PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR INDUSTRI FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 - 2016 - Wuwur, Anastasia Bribin; Frisdiantara, Christea; Sari, Ati Retna (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2017)
This study aims to examine and explain the effect of partially and the simultaneous influence of Corporate Social Responsibility (CSR) and Company Size on profitability in the Food and Beverage industry manufacturing companies listed on the Stock Exchange in the 2014-2016 period. This research uses quantitative methods, by testing classic assumptions, statistical analysis tools use multiple linear regression analysis. The sampling method of this research is purposive judgment sampling. The variables of this study consisted of Corporate Social Responsibility (CSR) as an independent variable and profitability as the dependent variable. The samples used were 12 companies. The analysis shows that partially and simultaneously CSR and company size affect profitability.